Learners’ experiences of an enhanced surgical skills training program for family physicians - Kornelsen, Jude; Geller, Brian; Janke, Fred; Iglesias, Stuart (Canadian Medical Education Journal, 2018)
Background: Family Physicians with Enhanced Surgical Skills (FPESS) have sustained rural operative care, including local access to caesarean section, in many communities across rural Canada and internationally. The contemporary role of FPESS within the health system, however, has not been without challenges. The 12-month Prince Albert Enhanced Surgical Skills (ESS) program intakes two learners a year and is one of only two accredited programs in Canada offering a scope of surgical practice beyond operative delivery. Methods: This paper highlights the results of an evaluation of graduates’ experiences of training and the post-training environment. Graduates were practicing in Western and Northern Canada after completing the ESS training program, specifically in British Columbia, Alberta, Manitoba, and the Northwest Territories. Results: Findings suggest the overall success of the program in meeting learners’ needs. There was a close match between the training curriculum and post-training practice. Conclusion: The findings from the post training experience suggest that sustainability of ESS is linked to 1) creating pathways to privileges between the ESS community and the Health Authorities, 2) building functional and trusting relationships with surgical specialists, and 3) creating a web of accessible effective rurally appropriate surgical Continuing Professional Development (CDP). Ongoing CPD is identified as essential in increasing the comfort of FPESS.